Photon interaction of molybdenum (Mo) based cesium tri-molybdate (Cs2Mo3O10) and disodium dimolybdate (Na2Mo2O7) single crystal scintillators. (November 2022) - Chaiphaksa, W.; Borisut, P.; Kim, H.J.; Kothan, S.; Kaewkhao, J.
Abstract: Both single crystals, molybdenum-based cesium tri-molybdate and disodium dimolybdate single crystal scintillators were investigated for gamma-rays interaction. The theoretical mass attenuation coefficients have been calculated by the WinXCom program. The 137 Cs source was used in the experiment that was irradiated with eight different photon energies using the Compton scattering technique. The theoretical result shows that the mass attenuation coefficient of both scintillators depends on photon energy and decreases with increasing of photon energy. The molybdenum-based cesium tri-molybdate shows higher values of the mass attenuation coefficient than disodium dimolybdate scintillator all the energy range. The experimental result shows the same trend and are good agreement with theoretical. The values of molybdenum-based cesium tri-molybdate show decreased from 22.15 to 7.7 ( × 10 −2  cm 2 /g) and the disodium dimolybdate scintillator shows decreased from 16.05 to 7.4 ( × 10 −2  cm 2 /g). Moreover, the partial interaction, the effective atomic number, and the effective electron density were also investigated. Highlights: Cs2 Mo3 O10 and Na2 Mo2 O7 crystal were analyzed for radiation shielding properties. The attenuation of samples was investigated in the energy ranging from 1keV to 100GeV. Effective electron density was comparable with experiment and theoretical values. Variation of MAC with effective atomic number for Na2 Mo2 O7 crystal were evaluated.